PHYSICAL PREPARATION IN PROFESSIONAL SURF ATHLETES: FICTION OR REALITY (Fiep Bulletin - online, 2013)
The objective of this research was to investigate the physical preparation of professional surf athletes. A sample of 51 professional surf athletes, nationals and foreign, from the male gender, selected intentionally, was utilized, with an average of age, stature, body mass, time of practice of the sport and time of practice as a professional athlete respectively of 23,1 ± 3,8 (years), 173,4 ± 6,2 (cm), 69,5 ± 5,5 (kg), 12,8 ± 4 (years) and 3,8 ± 2,9 (years). A questionary was utilized, with open and closed questions focusing on the aspects of the physical preparation of professional surf athletes, for the realization of the interviews. It was verified that 32 athletes do not have orientation of a professional (physical preparatory), which means, 63 (%) of the sample. Swimming represents the sport modality more utilized as a form of training, with an occurrence of 35,3 (%), followed by the gym with 33,3 (%), running with 29,4 (%), Yoga 21,7 (%) and bike, stretching and physical conditioning between 5 and 10 (%). It can be noticed that the bigger search for the modality swimming, is deeply related with the paddling in surf, the gym, for the acquisition of potency and muscle resistance, the run, for the aerobe aspect and the yoga do to the specific movements similar to the fundaments of surf, indicate that athletes and coaches, have an empiric knowledge based on the competitive practice of the modality. However a bigger diversity of studies about the physical requirements and about the variables involved with the sport may contribute to the development and improvement of the training programs.
Keywords: Surf; Physical preparation; sportive training